2009
DOI: 10.1007/s00125-009-1446-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of glucokinase activators GKA50 and LY2121260 on proliferation and apoptosis in pancreatic INS-1 beta cells

Abstract: Aims/hypothesis Glucokinase (GK), an enzyme that phosphorylates glucose to form glucose 6-phosphate, serves as the glucose sensor that regulates insulin secretion in beta cells. GK activators (GKAs) activate GK via binding to an allosteric site of the enzyme. GKAs increase glucosestimulated insulin secretion and decrease blood glucose levels. Using the differentiated beta cell line INS-1, we investigated the role of GKAs in promoting beta cell growth and survival and preventing beta cell apoptosis induced by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 34 publications
3
32
1
Order By: Relevance
“…Such lack of effect contrasts with recent reports showing that two GKAs (GKA50 and YH-GKA) that are chemically different from Ro acutely reversed the glucotoxic alterations of ␤-cell function (35,46). Although we tested the effect of Ro only in this protocol, other GKAs were found ineffective under similar conditions, indicating that the effect of GKA50 and YH-GKA unlikely resulted from GK activation (46).…”
Section: E636contrasting
confidence: 87%
See 1 more Smart Citation
“…Such lack of effect contrasts with recent reports showing that two GKAs (GKA50 and YH-GKA) that are chemically different from Ro acutely reversed the glucotoxic alterations of ␤-cell function (35,46). Although we tested the effect of Ro only in this protocol, other GKAs were found ineffective under similar conditions, indicating that the effect of GKA50 and YH-GKA unlikely resulted from GK activation (46).…”
Section: E636contrasting
confidence: 87%
“…If GKAs undoubtedly trigger liver steatosis (4,6,34), their potential toxicity to ␤-cells remains unclear (4,35,38,43,44,46). Thus, although some GKAs proved beneficial to ␤-cell survival and GSIS under glucotoxic conditions and in islets from T2D patients (8,35,46), their secondary failure during long-term treatment (22,31,47) reopened the question of their toxicity to ␤-cells. This possible caveat of GKAs has been previously considered nonrelevant on the ground that ␤-cell stimulation is reduced following the GKA-mediated reduction in glycemia (12).…”
Section: E636mentioning
confidence: 99%
“…Although chronic administration of GKA did not change b-cell mass in the above study, sustained exposure of INS1 cells to GKA promoted b-cell replication and, in addition, one compound, GKA50, reduced apoptosis (Nakamura et al 2009, Wei et al 2009). Further evidence to support the lack of detrimental effect on b-cell mass comes from demonstration that a short (3 days) treatment in vivo, when glucose concentration was high, increased the rate of b-cell proliferation (Nakamura et al 2009).…”
Section: Discussionmentioning
confidence: 55%
“…In a study of beta cell function, it was reported that a GKA stimulated insulin secretion in a Ca 2+ -dependent manner in rodent islets and MIN6 cells [13], and we and others have reported that GKAs promoted beta cell proliferation and increased production of IRS2 [11,14], which is critically required for beta cell growth and survival [3,[15][16][17]. However, the exact mechanisms by which GKAs stimulate beta cell function and proliferation are largely unknown.…”
Section: Introductionmentioning
confidence: 98%